Regional, Multilateral, and Unilateral Trade Policies on MERCOSUR for Growth and Poverty Reduction in Brazil - Harrison, Glenn W.; Rutherford, Thomas F.; Tarr, David; Gurgel, Angelo (World Bank, Washington, DC, 2014)
The authors estimate that the Free Trade Agreement of the Americas (FTAA), the EU-MERCOSUR agreement, and multilateral trade policy changes will all be beneficial for Brazil. The Brazilian government strategy of simultaneously negotiating the FTAA and the EU-MERCOSUR agreement, while supporting multilateral liberalization through the Doha Agenda, will increase the benefits of each of these policies. The authors estimate that the poorest households typically gain roughly three to four times the average for Brazil from any of the policies considerethe United States protects its most highly protected markets. Both the FTAA and the EU-MERCOSUR agreements are net trade-creating for the countries involved, but excluded countries almost always lose from the agreements. The authors estimate that multilateral trade liberalization of 50 percent in tariffs and export subsidies results in gains to the world more than four times greater than either the FTAA or the EU-MERCOSUR agreement. This shows the continued importance to the world trading community of the multilateral negotiations.